(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article examines anthroponyms based on ethnolinguistic factors and provides an overview of anthroponyms. In the example of "Temur’s rules" the features of famous nouns are revealed. The anthroponymic factors used in the play are mainly classified according to their scope and structure.